The Homosexual Exception? The Case of the Labouchère Amendment - William Fize (Cahiers Victoriens et Edouardiens)
The Labouchère amendment is often regarded as the piece of British legislation that criminalized male homosexuality. Indeed, while before it was passed, only sodomy had been a criminal offence, this amendment extended the scope of the criminal law by making a misdemeanour ‘the commission of or procures or attempts to procure the commission by any male person of any act of gross indecency with another male person’. As a consequence, it marked the beginning of a ‘homosexual exception’ surrounding its adoption as it was part of a wider bill—the Criminal Law Amendment Bill—, intended to protect younger girls from vice and prostitution. The bill took over four years to become law. The general consensus about the evils of male homosexuality was such that the amendment was adopted without any real debate in only four minutes. The broad spectrum of what was then considered a misdemeanour, whether committed by consenting adults in private or not, its vague phrasing made the prosecution of many men possible. However, that being said, in some respects there is a case for considering that English law regarding male homosexuality in Victorian England was not so ‘exceptional’ after all, and indeed could even be seen as representing a potentially more lenient evolution of the criminal law. However, this article argues that the ‘homosexual exception’ also needs to be seen from a different perspective: as the visible tip of the iceberg on sexual control.